Perspective directions of blockchain technology usage in digital marketing - O. P. Gavrilina; V. M. Komarov; A. A. Makarov (Путеводитель предпринимателя)
The article outlines the key directions for usage of the blockchain technology in digital marketing, describes the new business models of digital enterprises. The article characterizes the dynamics of changes in IT budgets of new business models of digital enterprises. Authors define the relationship of new business models in the digital economy. Authors suggest classification of enterprises based on approaches to the use of operational efficiency and customer experience. The directions ofdevelopment ofdigital enterprises are determined. Conclusions made on the structural changes ofdigital marketing.